Privacy's blueprint : the battle to control the design of new technologies - Hartzog, Woodrow, 1978- (Harvard University Press, 2018)
"Every day, Internet users interact with technologies designed to undermine their privacy. Social media apps, surveillance technologies, and the Internet of things are all built in ways that make it hard to guard personal information. And the law says this is okay because it is up to users to protect themselves--even when the odds are deliberately stacked against them. In Privacy's Blueprint, Woodrow Hartzog pushes back against this state of affairs, arguing that the law should require software and hardware makers to respect privacy in the design of their products. Current legal doctrine treats technology as though it were value-neutral: only the user decides whether it functions for good or ill. But this is not so. As Hartzog explains, popular digital tools are designed to expose people and manipulate users into disclosing personal information. Against the often self-serving optimism of Silicon Valley and the inertia of tech evangelism, Hartzog contends that privacy gains will come from better rules for products, not users. The current model of regulating use fosters exploitation. Privacy's Blueprint aims to correct this by developing the theoretical underpinnings of a new kind of privacy law responsive to the way people actually perceive and use digital technologies. The law can demand encryption. It can prohibit malicious interfaces that deceive users and leave them vulnerable. It can require safeguards against abuses of biometric surveillance. It can, in short, make the technology itself worthy of our trust."